2020
DOI: 10.1111/jcmm.15987
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0008003 facilitates tumorigenesis and development of non‐small cell lung carcinoma via modulating miR‐488/ZNF281 axis

Abstract: Non-small cell lung cancer (NSCLC) is a major cause of death associated with lung cancer, taking up over 85% of all lung cancers. 1 The survival of patients can be prolonged by diagnosing and treating the disease in the early stage. Nevertheless, the potential mechanism by which lung cancer evolves remains undocumented. Advances made in RNA research recently have contributed to identification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…A previous report revealed that circ_0008003 participated in NSCLC progress, and circ_0008003 promotes NSCLC cell invasion and proliferation in vitro 13 . Consistently, this study also found that the expression of circ_0008003 was highly expressed in NSCLC tissues and cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A previous report revealed that circ_0008003 participated in NSCLC progress, and circ_0008003 promotes NSCLC cell invasion and proliferation in vitro 13 . Consistently, this study also found that the expression of circ_0008003 was highly expressed in NSCLC tissues and cells.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have suggested that circRNAs can act as “microRNAs (miRNA) sponges” and participate in the regulation of tumor progress 9–12 . Hu et al found that circ_ 0008003 can participate in the regulation of the occurrence and development of NSCLC, and part of this is to act as a sponge of mir‐488, which was proven to be a tumor suppressor in some tumor diseases 13,14 . Although some studies have proposed relevant molecular mechanisms of circRNAs and miRNAs in NSCLC, further studies are needed to elucidate the regulatory network of circRNAs and their downstream factors.…”
Section: Introductionmentioning
confidence: 99%
“…3B: the vector panel appears similar to the sh-circ-0008003 panel in Fig. 2D in a previously-published article by different authors [ 2 ]; In Fig. 7B, the LINC00337 panel appears similar to the LINC01705 OE panel in Fig.…”
supporting
confidence: 58%
“…3B: the vector panel appears similar to the sh-circ-0008003 panel in Fig. 2D in a previously-published article by different authors [ 2 ];…”
mentioning
confidence: 60%